The Effect of Transformational Leadership on Innovative Work Behavior In SMEs: Test of a Mediating Model - Helmy, Irfan; Azizah, Siti Nur; Shalma, Ulfah Nur; Purnomo, Joko; Fitriani, Nugraheni (Journal of International Conference Proceedings, 2023)
In today’s advancing small-business competition, SME leaders are forced to build superior and innovative employees to sustain competitive advantages. This study scrutinises the link between transformational leadership and innovative work behavior by developing a mediating research model. The samples used in this study are 235 employees who work in the SME creative industries in Kebumen. Most of the respondents are working in the design and production divisions in the food, craft and fashion businesses. The analysis model used is the structural equation model (SEM) with Smart PLS software analysis. This study found that transformational leadership significantly affects innovative work behavior. Psychological safety and friendship at work significantly mediate the connection between transformational leadership and innovative work behavior. In addition, this research revealed that psychological safety shares a positive influence on friendship at work. This study provides insight for the transformational leader in the small business context to improve employees' innovative work behavior.Keywords: Transformational Leadership, Innovative Work Behavior, Psychological Safety, Friendship at Work.